Mass Spectrometry - Gross, Ju¨ rgen H. (Springer, 2017)
When non-mass spectrometrists are talking about mass spectrometry, it rather often sounds as if they were telling a story out of Poe’s Tales of Mystery and Imagination. Indeed, mass spectrometry appears to be regarded as a mysterious method, just good enough to supply some molecular weight information. Unfortunately, this rumor about the dark side of analytical methods may reach students way before their first contact with mass spectrometry. Possibly, some of this may have been bred by some mass spectrometrists who used to celebrate each mass spectrum they obtained from the very first gigantic machines of the early days. Of course, there were also those who enthusiastically started in the 1950s toward developing mass spectrometry out of the domain of physics to become a new analytical tool for chemistry. Within the more than a hundred years since J. J. Thomson’s seminal work, there has been a lot that has happened and a lot now to be known and learned about mass spectrometry.